A survey of multisensory VR and AR applications for cultural heritage. (February 2022) - Marto, Anabela; Gonçalves, Alexandrino; Melo, Miguel; Bessa, Maximino
Abstract: The use of technology in cultural heritage sites for end-users, like virtual audio-visual reconstructions, has become a common solution to improve the communication and perception between these spaces and their visitors. Since humans perceive the world with different senses and in real-time, to evoke more than one or two senses at a time can bring benefits for the user perception. Accordingly, some very different implementations unleashing multisensory experiences have been made. Aiming to understand how different stimuli are being evoked in multisensory experiences to enhance cultural heritage experiences, and how these implementations are being evaluated, this paper presents a systematic review of technological multisensory applications in cultural heritage. Thus, the collected and analyzed data, focused on technologies used, purpose of the experience, stimuli explored, evaluation process, main findings obtained, and limitations found, will provide valuable information for further implementations. The overall results unleash the wide diversity available for multisensory implementations, from technological solutions to available content for users. Covering the pros and cons of such diversity, this study sustains the use of multisensory applications in cultural heritage as a powerful tool to enrich users' visits. Graphical abstract: Highlights: Systematic review on Multisensory VR and AR implementations in Cultural Heritage. Analysis of evoked stimuli and of what technologies were used to evoke each stimulus. Detailed analysis of the purpose of each implementation and of conducted evaluations. Mention to studies' main findings and main limitations found. Discussion related to analyzed multisensory studies.